Tafsir of Qur'anic Verses on Consumption - Samsuriadi Samsuriadi; Achmad Abubakar; Rusydi Khalid (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
The Qur'an is a source of excavation and development of Islamic teachings in various dimensions of human life. This paper tries to develop economic studies from an economic point of view based on the interpretation of the Qur'an. As a methodology, tafsir plays an important role in order to develop the discipline of Islamic economics. The model of economic interpretation derived from the thematic interpretation of the Qur'an is developed through four phases including; Classification of Qur'anic verses related to economics, understanding them based on chronology, micro and macro context, and socioeconomic contextualization. In summary, this paper reveals that consumption behavior in the Qur'an is harmoniously regulated, gradual and systematically to propose a new model of consumption for Muslims through Islamic consumption behavior.